THE EFFECT OF POPULATION GROWTH AND INFLATION ON ECONOMIC GROWTH IN EAST ASIA - Steven, Nikolas; Wijasari, Michelle Susanto; Putera, Evan Kaban; Vincenttius, Ferry Ferdinand (FEB Universitas Sam Ratulangi Manado, 2024)
Abstract . This study delves into the longstanding debate surrounding the impact of population growth and inflation on economic growth, particularly focusing on East Asia. Past studies on the impact of population growth and inflation on economic growth have yielded contradictory results, with some indicating positive effects, others suggesting negative effects, and some find no significant impact at all. This study aims to find whether population growth and inflation affects the economic growth of East Asia using panel data regression. The data are taken from sample of East Asian countries from 2001-2022 annually. The findings reveal that when population growth and inflation are considered together, they have a significant effect on the economic growth of East Asia. Specifically, it was found that population growth has a significant positive relationship on the economic growth of East Asia. Conversely, inflation does not have a significant effect on the economic growth of East Asia. Abstrak. Studi ini menyelidiki perdebatan lama seputar dampak pertumbuhan penduduk dan inflasi terhadap pertumbuhan ekonomi, khususnya dengan fokus di Asia Timur. Penelitian-penelitian terdahulu mengenai dampak pertumbuhan penduduk dan inflasi terhadap pertumbuhan ekonomi memberikan hasil yang kontradiktif, ada yang menunjukkan dampak positif, ada pula yang menunjukkan dampak negatif, dan ada pula yang tidak menunjukkan dampak signifikan sama sekali. Penelitian ini bertujuan untuk mengetahui apakah pertumbuhan penduduk dan inflasi berpengaruh terhadap pertumbuhan ekonomi Asia Timur dengan menggunakan regresi data panel. Data diambil dari sampel negara-negara Asia Timur dari tahun 2001-2022 setiap tahunnya. Temuan mengungkapkan bahwa jika pertumbuhan penduduk dan inflasi digabungkan, keduanya mempunyai pengaruh yang signifikan terhadap pertumbuhan ekonomi Asia Timur. Secara khusus ditemukan bahwa pertumbuhan penduduk memiliki hubungan positif yang signifikan terhadap pertumbuhan ekonomi Asia Timur. Sebaliknya inflasi tidak berpengaruh signifikan terhadap pertumbuhan ekonomi Asia Timur.